JOB CREATION LAW: HEALTHY INVESTMENT CLIMATE OR INJURED CLIMATE COMMITMENT? - Cindy Cherya (President University, 2019)
To overcome the problem of overlapping regulations and complexities of investment in Indonesia, on 5th October 2020, the Jokowi government passed Law Number 11 of 2020 concerning Job Creation (“Job Creation Law”), which is still a controversy to this day. This law has drawn broad criticism, particularly regarding the formal law-making and its problematic substances. Critics argue the legal drafting process is not in accordance with the characteristic of good law making aspired by the 1945 Constitution and Law Number 12 Year 2011 concerning the Establishment of Legislation (“Establishment of Legislation Law”). Noting that the academic text of this law does not address the importance of protecting forests and the environment, but only focuses on increasing economic development and investment. The public is faced with a dilemma of trust whether there is a trade between economic growth and environmental sustainability that is hidden by the government. The pro-deforestation articles in this law generate fundamental changes in the framework of protecting Indonesia's environment which it is feared could open the door to massive deforestation and have a global impact on violating Indonesia's climate commitment under Paris Agreement. Through this writing, the author questions the consistency of the Indonesian government in carrying out its climate commitments to prevent future deforestation. The authors will identify weakening instruments for environmental protection and forest management under the Job Creation Law as well as their impact to environmental protection efforts and Indonesia's future climate commitments. At the end of this study, the author found that due to weakening of forest and environmental protection instruments, Indonesia risks failing to meet its climate commitments targeted in the first Nationally Determined Contribution (NDC) to reduce deforestation to below 3.25 million hectares by 2030 or a maximum of 325,000 hectares / year during 2020 to 2030 either on their own or with international assistance.